What does the Acute Respiratory Distress Syndrome trial (ART) teach us?—it is time for precision medicine and precision trials in critical care! - Fumagalli, Jacopo; Berra, Lorenzo (Journal of Thoracic Disease; Vol 10, No 3 (March 31, 2018): Journal of Thoracic Disease, 2018)
Acute respiratory distress syndrome (ARDS) affects a remarkable proportion of patients admitted to the intensive care unit (ICU) and according to a recent international survey, mortality attributable to ARDS remains high (≈40%) (1).